Pengembangan Sumber Daya Manusia di Industri Otomotif Melalui Institut Otomotif Indonesia - Mujiyono Mujiyono; Sonny Taufan (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
Creating an organization or company, both in terms of form and purpose, is made based on a vision to fulfill human interests. In its implementation, the mission is managed by human resources. In addition, human resources are a central factor in an organization or company. So that the need for effective and efficient human resource management to achieve the company's goals optimally. This research is a case study using primary data collected from interviews and observations. In addition, it also uses supporting data, namely secondary data obtained from the results of previous studies and literature studies. This research aims to study and identify human resource development systems in the automotive industry by linking IOI's role in preparing competent human resources in the automotive industry in Indonesia. The results of the study show that the development and improvement of HR competencies in the automotive industry can be carried out by: (1) Competency-based education and training systems; (2) Organizing training with a 3 in1 system; (3) Reskilling and Upskilling; and (4) participating in the PIDI 4.0 ecosystem. In addition, there is a need for good coordination and cooperation between IOI organizations and stakeholders such as academics, business, government, and society in order to be able to create competent human resources to advance the national automotive industry.